Parent Education Parent Counseling; A Selective Bibliography. Exceptional Child Bibliography Series No. 631. - Council for Exceptional Children, Reston, VA. Information Center on Exceptional Children; Council for Exceptional Children, Reston, VA. Information Center on Exceptional Children ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
The selected bibliography on parent education and parent counseling contains approximately 98 abstracts with indexing information explained to be drawn from the computer file of abstracts representing the Council for Exceptional Children Information Center's complete holdings as of August, 1972. Abstracts are said to be chosen using the criteria of availability of document to user, currency, information value, author's reputation, and classical content. Preliminary information explains how to read the abstract (a sample abstract is included which identifies the different parts of the abstract), how to use the author and subject indexes, how to purchase documents through the Educational Resources Information Center Document Reproduction Service (an order blank is provided), an order blank for Exceptional Child Education Abstracts in which the abstracts are originally published, a list of indexing terms searched to compile the bibliography, and a list of journals from which articles are abstracted for the bibliography. Publication date of documents abstracted ranges from 1952 to 1971. (CB)
Availability: The Council for Exceptional Children, 1411 S. Jefferson Davis Highway, Arlington, Virginia 22202.
Sponsoring Agency: Bureau of Education for the Handicapped (DHEW/OE), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Abstracts; Annotated Bibliographies; Exceptional Child Education; Handicapped Children; Parent Child Relationship; Parent Counseling; Parent Education; Parent Influence; Parent Role; Parent School Relationship